Illustrated Electronic Module to Improve Elementary School Students' Creative Thinking Skills - Suantini, I Gusti Ayu Ketut Ari; Antara, Putu Aditya; Trisna, Gusti Ayu Putu Sukma (Universitas Pendidikan Ganesha, 2022)
Low learning outcomes are caused because students need to have the ability to think creatively. The findings state that students need help to express ideas or ideas in learning activities so that learning activities do not run optimally. This study aims to develop an electronic pictorial module to improve the creative thinking skills of fourth-grade elementary school students. This type of research is developed with the ADDIE model. The research subjects were two material expert lecturers, two media expert lecturers, and one practitioner. The test subjects totaled 26 students—data collection using the questionnaire method. The instrument used is the rating scale instrument. Data analysis techniques are qualitative descriptive statistical analysis, quantitative descriptive, and inferential statistics. The results of the research are media experts' assessment of 4.8 (very good), material experts’ 4.9 (very good), and practitioner results of 5 (very good). The results of the 2-way (2-tailed) significance value were 0.000 <0.05 so that there were differences in the results of the creative thinking abilities of fourth-grade elementary school students after learning to use pictorial electronic modules (e-modules). It was concluded that the pictorial E-Module effectively increases the results of creative thinking skills.